Kombinasi Sofosbuvir-Ledipasvir dan Sofosbuvir- Daclatasvir pada Pengobatan Pasien Hepatitis C di Indonesia - Sulaiman, Andri Sanityoso, Dr; Hasan, Irsan, Dr; Lesmana, Cosmas Rinaldi Adithya, Dr; Kurniawan, Juferdy, Dr; Aprilicia, Gita; Nugroho, Yayah, Dr; Wahyuni, Nunuk Tri, Dr; Sulaiman, Budiman Sujatmika (UI Scholars Hub, 2023)
Introduction. Direct-acting antivirals (DAAs) has been developed for treatment hepatitis C virus (HCV). Therapy of HCV using DAA has shown high sustained virologic response (SVR) and shortening duration of therapy. Sofosbuvir-ledipasvir (SOF/LDV) is fixed dose combination tablet of DAAs which recommended for genotype 1, 4, 5, and 6 infected patients. In developing countries, SOF/LDV still can be used as cost-effective regimen in all genotype compared with sofosbuvir-daclatasvir (SOF/ DCV). This study aimed to evaluate the efficacy of combination sofosbuvir-ledipasvir in all genotypes of HCV patients compared with available DAA in Indonesia (sofosbuvir- daclatasvir). Methods. A retrospective study was conducted among patients who received HCV therapy in Klinik Hati and Cipto Mangunkusumo Hospital during January until December 2017. Demographic data, baseline characteristics virus, and baseline characteristics laboratory were collected from medical record. Quantitative polymerase chain reaction (PCR) for HCV RNA were assessed at the end point of study. The efficacy of SOF/LDV and SOF/DCV were carried out by sustained virological response at 12 weeks (SVR-12). Results. A total of 214 HCV patients were include in this study. Sixty-nine patients treated with SOF/LDV, whereas 145 patients treated with SOF/DCV. In group of SOF/LDV, 20 (29%) patients had an experience therapy, 9 (13%) received 24-week therapy, 26 (37.7%) patients observed with cirrhosis. In group of SOF/DCV, 24 (16.6%) patients had an experience therapy, 38 (26.2%) received 24-week therapy, 41 (28.3%) patients observed with cirrhosis. The patients were dominated by HCV genotype 1 in both of group SOF/LDV and SOF/DCV (63.7% vs. 67.6%). All patients had undetected HCV RNA virus after the combination therapy of SOF/LDV, with the SVR-12 rate was 69 (100%) patients. Meanwhile, SVR-12 rate was achieved in 142 (97.9%) patients in group SOF/DCV. Conclusion. SOF/LDV is effective in all genotypes of HCV patients and the cost fix dose combination of SOF/LDV more affordable to patients in developing countries compared with SOF/DCV regimen.